2008
DOI: 10.1007/s00213-008-1224-6
|View full text |Cite
|
Sign up to set email alerts
|

Chronic intermittent cold stress and serotonin depletion induce deficits of reversal learning in an attentional set-shifting test in rats

Abstract: Rationale-Chronic stress perturbs modulatory brain neurotransmitter systems, including serotonin (5-HT), and is a risk factor for psychiatric disorders such as depression. Deficits in cognitive flexibility, reflecting prefrontal cortical dysfunction, are prominent in such disorders. Orbitofrontal cortex (OFC) has been implicated specifically in reversal learning, a form of cognitive flexibility modulated by 5-HT.Objectives-Assess the effects of chronic intermittent cold (CIC) stress, a potent metabolic stresso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
137
4
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(164 citation statements)
references
References 75 publications
19
137
4
1
Order By: Relevance
“…However, previously stressed mice committed fewer errors than did unstressed mice later in reversal learning, when perseveration had ceased (i.e., accuracy ≥ 50 %), an effect prevented by brain-derived neurotrophic factor infusions into the ventral medial prefrontal cortex (Graybeal et al, 2011). The effects of other, longer chronic-stress protocols on reversal learning have been inconsistent (Bondi et al, 2008;Liston et al, 2006), although impaired reversal learning is consistently observed following some chronic stress protocols (Danet et al, 2010;Lapiz-Bluhm et al, 2009). The time frame of the acute stress-induced facilitation of reversal learning was much shorter in the present experimental design: Rats were subjected to acute stress for 30 min Stress refers only to stress on the reversal test day (see Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, previously stressed mice committed fewer errors than did unstressed mice later in reversal learning, when perseveration had ceased (i.e., accuracy ≥ 50 %), an effect prevented by brain-derived neurotrophic factor infusions into the ventral medial prefrontal cortex (Graybeal et al, 2011). The effects of other, longer chronic-stress protocols on reversal learning have been inconsistent (Bondi et al, 2008;Liston et al, 2006), although impaired reversal learning is consistently observed following some chronic stress protocols (Danet et al, 2010;Lapiz-Bluhm et al, 2009). The time frame of the acute stress-induced facilitation of reversal learning was much shorter in the present experimental design: Rats were subjected to acute stress for 30 min Stress refers only to stress on the reversal test day (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent report has shown that infusions of corticotropin-releasing factor (CRF) into the locus coeruleus produce a complex modulation of setshifting and reversal learning in rats (Snyder, Wang, Han, McFadden, & Valentino, 2012): Rats infused with higher doses of CRF displayed enhanced reversal learning, whereas a low dose enhanced the set-shifting component of the same task (Snyder et al, 2012). Serotonergic, dopaminergic, and glutamatergic systems are also involved in reversal learning (Balschun et al, 2010;Bannerman, Deacon, Seeburg, & Rawlins, 2003;Boulougouris & Robbins, 2010;Floresco et al, 2009;Lapiz-Bluhm et al, 2009;Robbins & Roberts, 2007). Therefore, a direction for further research could be to manipulate these neurotransmitter systems in order to assess the roles Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is now considerable evidence linking reversal learning with 5-HT mechanisms, including in rodents (Masaki et al, 2006;Boulougouris et al, 2008;Lapiz-Bluhm et al, 2009), non-human primates (Clarke et al, 2004(Clarke et al, , 2005Walker et al, 2009), and human beings (Park et al, 1994;Rogers et al, 1999a;Evers et al, 2005) based on pharmacological, neurochemical and dietary manipulations, and evidence of genetic polymorphisms in rhesus monkeys (Izquierdo et al, 2007). Generally, reducing brain serotonin, especially in specific regions such as the OFC (eg Clarke et al, 2004), impairs reversal learning.…”
Section: Translational Models Of Impulsivity and Compulsivitymentioning
confidence: 99%
“…76 Additionally, online microdialysis can be performed in experimental animals during behavioral tasks. 38,39 High temporal resolution and multiplexed measurements will be vital to understanding how behaviorally relevant information is encoded in chemical neurotransmission. 77,78 ■ METHODS Animals.…”
Section: ■ Conclusion and Future Prospectsmentioning
confidence: 99%